Jorge SEMPRÚN / Manuel AZNAR SOLER y Felipe NIETO (eds.).— Teatro completo. Sevilla: Renacimiento, 2021, 352 pp. - Sevilla Llisterri, Gabriel (Signa: Revista de la Asociación Española de Semiótica, 2023)
Reseña